Social Media and Civil Society in Japan - Kaigo, Muneo (Springer Singapore : Imprint: Palgrave Macmillan, 2017)
This book offers an overview of social media usage in Japan and describes its role in society during mid-level disruptions by natural disasters. Conceived during and after the Great East Japan Earthquake that devastated large portions of the north-eastern area of Japan, this volume addresses the links between Japanese civil society and the social media scene, using both traditional hypothesis testing, social surveys and large-scale big data analysis to provide insight into the development of an online community for connecting citizens. Considering the connection of civil society organizations, citizens and local governments through online communication, notably social media, and how to promote higher levels of citizen engagement in Japan, it offers solutions for a more prepared, resilient communication network among citizens in case of another large scale disaster.
Keywords: Social sciences.; Ethnology -- Asia.; Social media.; Political communication.; Communication.; Sociology.; Mass media.; elektronické knihy; electronic books